2017
DOI: 10.1200/jco.2017.35.15_suppl.4515
|View full text |Cite
|
Sign up to set email alerts
|

Epacadostat plus pembrolizumab in patients with advanced RCC: Preliminary phase I/II results from ECHO-202/KEYNOTE-037.

Abstract: 4515 Background: Epacadostat (E) is a potent oral inhibitor of indoleamine 2,3-dioxygenase 1 (IDO1), a tryptophan-catabolizing enzyme that induces immune tolerance by T-cell suppression. Preclinical and clinical data suggest that epacadostat has antitumor activity when combined with checkpoint inhibitors, including the PD-1 inhibitor pembrolizumab (P). ECHO-202/KEYNOTE-037 is an ongoing open-label, phase 1/2 (P1/2) study evaluating E + P in multiple tumor types. We report preliminary P1/2 efficacy and safety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…For example, the phase 1/2 ECHO‐202/KEYNOTE‐037 study evaluates the efficacy, tolerability and safety of combining the IDO inhibitor epacadostat plus pembrolizumab in patients with various tumor entities such as advanced RCC, urothelial carcinoma, triple‐negative breast and ovarian cancer, head and neck tumors and non‐small cell lung cancer (NCT02178722). Regarding advanced RCC, preliminary results demonstrated an ORR in patients with 0‐1 prior lines of treatment of 47% (CR in 5%) and a disease control rate (DCR) of 58%, confirming responses regardless of PD‐L1 expression …”
Section: Discussionmentioning
confidence: 79%
“…For example, the phase 1/2 ECHO‐202/KEYNOTE‐037 study evaluates the efficacy, tolerability and safety of combining the IDO inhibitor epacadostat plus pembrolizumab in patients with various tumor entities such as advanced RCC, urothelial carcinoma, triple‐negative breast and ovarian cancer, head and neck tumors and non‐small cell lung cancer (NCT02178722). Regarding advanced RCC, preliminary results demonstrated an ORR in patients with 0‐1 prior lines of treatment of 47% (CR in 5%) and a disease control rate (DCR) of 58%, confirming responses regardless of PD‐L1 expression …”
Section: Discussionmentioning
confidence: 79%
“…In the clinic, IDO1 inhibition alone has little anticancer effect in a majority of patients (6,7). However, early-phase studies demonstrating encouraging response rates and durability of responses suggested that the addition of IDO1 inhibitors to programmed cell death protein 1 (PD-1) or programmed death-ligand 1 (PD-L1) inhibition may enhance the efficacy of checkpoint blockade alone (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…• Epacodostat/pembrolizumab, solid tumors including RCC • Phase 1/2 (ECHO-202/KEYNOTE-037/NCT02178722) [99] • ORR in 19 RCC pts with 0-1 prior tx: 47% (1 CR, 8 PR)…”
Section: 4-184)mentioning
confidence: 99%
“…Ongoing trials are also combining checkpoint inhibitors with novel/ investigational immunotherapies. These include: NKTR 214 (pegylated IL-2), an agonist of CD-122 that stimulates CD-8+ and NK cells [96]; pegilodecakin, a pegylated human IL-10, as IL-10 receptors are expressed on activated CD8+ cells [97]; CPI-444, an oral adenosine A2a receptor antagonist [98]; and epacadostat, an inhibitor of indoleamine 2,3-dioxygenase 1, a tryptophan-catabolizing enzyme that induces immune tolerance by T-cell suppression [99]. Preliminary results from a phase 1/2 study for epacadostat combined with pembrolizumab in advanced RCC reported an ORR of 47% [99]; however, a recent phase 3 trial of this combination in patients with melanoma failed to meet its primary endpoint of improved PFS relative to pembrolizumab monotherapy [100].…”
Section: Novel Immunotherapy Combinationsmentioning
confidence: 99%